2010
DOI: 10.1111/j.1365-2966.2010.16617.x
|View full text |Cite
|
Sign up to set email alerts
|

Spitzer mid-infrared observations of seven bipolar planetary nebulae

Abstract: We have investigated the mid‐infrared (MIR) and visual structures of seven bipolar planetary nebulae (BPNe), using imaging and spectroscopy acquired using the Spitzer Space Telescope (SST), and the Observatorio Astronomico Nacional in Mexico. The results show that the sources are more extended towards longer MIR wavelengths, as well as having higher levels of surface brightness in the 5.8‐ and 8.0‐μm bands. It is also noted that the 5.8 μm/4.5 μm and 8.0 μm/4.5 μm flux ratios increase with increasing distance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 129 publications
1
13
0
Order By: Relevance
“…Previous optical imagery of this PN reveals a bright, central ring-shaped morphology and open bipolar lobes The physical structure and internal kinematics were studied by Vázquez et al (2004). Despite these multiwavelength studies, the properties and exact structure of NGC 6445 are still poorly defined (Phillips & Ramos-Larios 2010). Our NOT ALFOSC wide-field optical images show that NGC 6445 has an irregularly shaped central region with a size of ∼40″×50″, where the [O III] emission dominates, while the [N II] emission is much more extended and defines an overall bipolar morphology ( Figure 1).…”
Section: Ngc 6445mentioning
confidence: 84%
See 1 more Smart Citation
“…Previous optical imagery of this PN reveals a bright, central ring-shaped morphology and open bipolar lobes The physical structure and internal kinematics were studied by Vázquez et al (2004). Despite these multiwavelength studies, the properties and exact structure of NGC 6445 are still poorly defined (Phillips & Ramos-Larios 2010). Our NOT ALFOSC wide-field optical images show that NGC 6445 has an irregularly shaped central region with a size of ∼40″×50″, where the [O III] emission dominates, while the [N II] emission is much more extended and defines an overall bipolar morphology ( Figure 1).…”
Section: Ngc 6445mentioning
confidence: 84%
“…There are very faint, extended structures in the H 2 emission, which are almost overwhelmed by bright field stars but are still marginally visible in the color-composite image, where the extended H 2 emission seems to be limb-brightened. The Spitzer mid-IR images show that NGC 6445 is more extended in the 8.0 μm emission (Phillips & Ramos-Larios 2010), which fills the halo region defined by the seemingly limb-brightened H 2 emission ( Figure 6, right).…”
Section: Ngc 6445mentioning
confidence: 94%
“…Based on observations of its density, the nebula appears to be evolved. The mid-IR Spitzer image by Phillips & Ramos-Larios (2010) shows differences in the optical and mid-IR distributions, and the presence of strong 8.0 µm emission outside the central nebula. They argue the possibility that this extended mid-IR emission derives from a cylinder of neutral material that would be responsible for the large-scale collimation of the optical structures.…”
Section: Ngc 6445mentioning
confidence: 98%
“…Mid-infrared (mid-IR) spectroscopy is a powerful tool for the study of the thermal and molecular emission from PNe, since such observations are much less affected by dust extinction. Mid-IR studies of PNe have focused on imaging surveys (e.g., Hora et al 2004;Phillips & Ramos-Larios 2008;Zhang & Kwok 2009;Phillips & Ramos-Larios 2010;Zhang, Hsia & Kwok 2012), but mid-IR spectroscopy of PNe has only been carried out for individual objects for which chemical abundances and H2 excitation temperatures were obtained (Cox et al 1998;Matsuura & Zijlstra 2005;Hora et al 2006;Phillips, Ramos-Larios & Guerrero 2011). Currently, mid-IR studies of the excitation temperature of H2 in PNe are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Phillips & Ramos-Larios (2008a) analyzed quantitatively IRAC images of 18 PNe and suggest that PAH emission from PDRs contributes significantly to the observed mid-IR fluxes. Phillips & Ramos-Larios (2010) extended their analysis to seven bipolar PNe, assessing the roles of PAH emission from PDRs and shock excited H 2 emission, and discussing the color variations from the cores to the lobes. Cerrigone et al (2008) analyzed IRAC images, in conjunction with 4.8 and 8.6 GHz radio continuum observations, of the bipolar PN IC 4406, and concluded that there exist at least three dust components at temperatures ranging from 57 to 700 K.…”
Section: Irac Observations Of Pnementioning
confidence: 99%